2015
DOI: 10.1038/nature15757
|View full text |Cite
|
Sign up to set email alerts
|

Widespread exploitation of the honeybee by early Neolithic farmers

Abstract: The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(86 citation statements)
references
References 28 publications
(28 reference statements)
5
72
0
8
Order By: Relevance
“…Dudd and Evershed 1998;Evershed et al 2002;Copley et al 2003;Evershed et al 2008;Dunne et al 2012;Debono Spiteri et al 2016). Likewise, aquatic products (Patrick et al 1985;Hansel et al 2004;Craig et al 2007;Hansel and Evershed 2009;Shoda et al 2017), plant oils and waxes denoting vegetable and plant oil consumption/ processing (Evershed et al 1991;Copley et al 2001a;Copley et al 2001b;Reber et al 2004;Copley et al 2005;Cramp et al 2011;Dunne et al 2016) and beeswax (Heron et al 1994;Charters et al 1995;Evershed et al 1997b;Regert et al 2001;Evershed et al 2003;Roffet-Salque et al 2015), resins, tars and bitumen (Beck et al 1989;Mills and White 1989;Evershed et al 1997a;van Bergen et al 1997;Urem-Kotsou et al 2002;Stern et al 2003;Buckley et al 2004;Stern et al 2008;Connan et al 2013;Brown et al 2014: Brettell et al 2014 have been identified in connection with a wide range of technological and cultural activities. On a broader scale, lipid residue analyses can provide insight into the domestication of plants and animals, the development of animal husbandry practices and ecological and environmental changes through time (Evershed 2008b;Evershed et al 2008;…”
Section: Introductionmentioning
confidence: 99%
“…Dudd and Evershed 1998;Evershed et al 2002;Copley et al 2003;Evershed et al 2008;Dunne et al 2012;Debono Spiteri et al 2016). Likewise, aquatic products (Patrick et al 1985;Hansel et al 2004;Craig et al 2007;Hansel and Evershed 2009;Shoda et al 2017), plant oils and waxes denoting vegetable and plant oil consumption/ processing (Evershed et al 1991;Copley et al 2001a;Copley et al 2001b;Reber et al 2004;Copley et al 2005;Cramp et al 2011;Dunne et al 2016) and beeswax (Heron et al 1994;Charters et al 1995;Evershed et al 1997b;Regert et al 2001;Evershed et al 2003;Roffet-Salque et al 2015), resins, tars and bitumen (Beck et al 1989;Mills and White 1989;Evershed et al 1997a;van Bergen et al 1997;Urem-Kotsou et al 2002;Stern et al 2003;Buckley et al 2004;Stern et al 2008;Connan et al 2013;Brown et al 2014: Brettell et al 2014 have been identified in connection with a wide range of technological and cultural activities. On a broader scale, lipid residue analyses can provide insight into the domestication of plants and animals, the development of animal husbandry practices and ecological and environmental changes through time (Evershed 2008b;Evershed et al 2008;…”
Section: Introductionmentioning
confidence: 99%
“…Honeybees have probably been managed by European farmers since the Neolithic age [8], and feral populations occurred in northern Europe until the introduction of Varroa mites [9]. Hence, honeybees have a long history of coexistence with wild flower-visiting insects.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of the lost-wax technique at Mehrgarh could have been triggered by several factors. The availability of beeswax is attested in the Near East at this period28. Second, recent works have proposed that lost-wax casting has been adopted more for the central role of beeswax as a ritually important material than for a technical need29.…”
Section: Discussionmentioning
confidence: 99%